The Role of Parents in their Children’s Learning English in Mentawai - Melvina, Melvina; Lidya, Marina; Taileleu, Norlina (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
The role of parents is crucial aspects for students in learning English. Parents are the central factor in providing a good environment for the children. They are also one of the great boosters for students to motivate in learning. However, many parents are still not aware of their role. It can be happened because of some factors, such as parents’ educational background, and financial condition. This study aims to investigate whether parents in Mentawai play their role as educators, motivators, facilitators, and advisors to their children in learning English. This study applied quantitative descriptive research with a survey method. Thirty-one senior high school students in Pagai Utara Selatan Mentawai Island were enrolled using a conventional sampling technique. This study used a questionnaire for the role of parents to collect the data. Then, data gathered from the questionnaire were analyzed by applying descriptive statistics. The findings revealed that parents in this study do not fully play their role as educators, motivators, and facilitators. However, the parents of students in this study have played their role as advisors.